Hak Cipta sebagai Objek Jaminan Fidusia - Rany Kartika Sari (Lex Renaissance, 2016)
AbstractThis Thesis is conducted to assess the implementation of Article 16 Section (3) Number 28 Year 2014. It stated that copyright could be as fiduciary. The problem statements are: Could the copyright as the object of fiduciary be executed if the debtor breachs the contract?; How is the role of the notary in order to create burden of fiduciary deed the copyright?. The analyzes are normative qualitative and futuristic. The result of the thesis shows that copyright which is secured fiduciary, it could be executed based on Article 29 Law Number 42 Year 1999 about Fiduciary. The reason is the economic right of the copyright could be secured (it is an intangible object). Besides, related to the notary’s deed, the authority of the notary to make burden of fiduciary deed has already been mentioned on the Article 5 Section (1) about Fiduciary, thus there is no reason for the notary to reject for creating deed of fiduciary with copyright as the object. It is neccessary for the notary that having deep acknowledgement related to the copyright theoritically and practically.  Key words: Copyright, Fiduciary, Deed